Adaptive real-time optimal energy management strategy based on equivalent factors optimization for hybrid fuel cell system. (19th January 2021) - Gao, Huizhong; Wang, Zhijie; Yin, Shaoping; Lu, Jun; Guo, Zhaoyuan; Ma, Weifeng
Abstract: Fuel cell, a new kind of energy supply equipment, has several advantages such as high efficiency, low noise, and no emission. Proton exchange membrane fuel cell (PEMFC) is considered to have the potential to take the place of the conventional engine on unmanned underwater vehicle (UUV). Besides the power sources in the hybrid power system, the energy management system (EMS) is crucial to operating performance. In this paper, an on-line adaptive equivalent hydrogen consumption minimization strategy (ECMS) is proposed to solve the problem of prior knowledge demand and poor adaptability of current energy management algorithms. In this presented method, a battery state of charge (SOC) constituted penalty term is designed to calculate the equivalent factor (EF), and then the equivalent factor obtained by optimization is substituted into the original objective equation to realize the real-time energy regulation. In this paper, a typical UUV load curve is used to verify the control effect under different working conditions, and the performance is compared with three conventional algorithms'. Simulation results show that the hydrogen consumption of proposed algorithm is close to the optimal solution obtained in offline environment, and it is reduced by more than 3.79% compared with the traditional online methods. Highlights: A new penalty term for equivalent hydrogen consumption strategy is proposed. This proposed EMS can realize optimal control without prior knowledge and training. This method has good robustness in diverse operating conditions. Hydrogen consumption is close to that of offline-PMP algorithm.